2016
DOI: 10.1177/1541931213601331
|View full text |Cite
|
Sign up to set email alerts
|

Better off Alone

Abstract: It is well known that traffic collisions can easily occur when a driver’s attention is consumed by task irrelevant information (e.g. cellphone, or billboards). Is it possible though that drivers will fail to identify certain hazards or traffic signals because their focus is consumed by other, equally, pertinent events on the road? In order to answer this question, the present study adopted a simulated driver awareness task which used Satisfaction of Search to show that when drivers are faced with a single low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Drivers may also search for these targets while conducting ill-advised activities such as talking or texting on a cell phone -activities that further reduce the probability of spotting a hazard (Strayer, Drews, & Johnston, 2003). Recent evidence shows that SSM errors are possible when traffic is at a standstill (Sall & Feng, 2016). Our results suggest that these errors are even more likely when traffic is moving.…”
Section: Discussionsupporting
confidence: 47%
“…Drivers may also search for these targets while conducting ill-advised activities such as talking or texting on a cell phone -activities that further reduce the probability of spotting a hazard (Strayer, Drews, & Johnston, 2003). Recent evidence shows that SSM errors are possible when traffic is at a standstill (Sall & Feng, 2016). Our results suggest that these errors are even more likely when traffic is moving.…”
Section: Discussionsupporting
confidence: 47%
“…Drivers may also search for these targets while conducting ill-advised activities such as talking or texting on a cell phone-activities that further reduce the probability of spotting a hazard (Strayer, Drews, & Johnston, 2003). Recent evidence has shown that SSM errors are possible when traffic is at a standstill (Sall & Feng, 2016). Our results suggest that these errors are even more likely when traffic is moving.…”
Section: Discussionmentioning
confidence: 71%
“…The interaction between these two types of processing is especially relevant in young drivers. Not only do young drivers have less experience with hazardous situations (and therefore possess less knowledge on how to avoid or mitigate such hazards), they may be at risk of becoming fixated on overt, salient hazards at the expense of missing less salient driving hazards (Sall & Feng, 2016). In basic visual attention research, it has been shown that topdown processes can override bottom-up attributes (Yantis & Egeth, 1999).…”
Section: Introductionmentioning
confidence: 99%